Nurses' Late-Life Depression Knowledge and Attitudes Toward Depression: A Cross-Sectional Study - Cheng-Hua Ni RN, MSN; Shu-Liu Guo RN, PhD; Chia-Yu Chao RN, BSN; Chia-Hui Wang RN, PhD; Sri Susanty RN, MS; Yeu-Hui Chuang RN, PhD (SAGE Publishing, 2020)
Depression in older population is more common now. Due to increasing numbers of older patients in hospitals, nurses have more opportunities to care for these patients. Therefore, nurses should have correct knowledge of late-life depression and more favorable attitudes about depression. The study aimed to understand hospital nurses' knowledge level of late-life depression and attitudes about depression. A cross-sectional research design was used. A convenience sample of 307 nurses from 3 hospitals in Taiwan was recruited. Nurses scored 55.15% in the Late-Life Depression Quiz. The average score of the Revised Depression Attitude Questionnaire was 71.76 (SD = 6.13). The study also found that hospital nurses had more favorable attitudes about depression when their late-life depression knowledge was higher; their interest level in providing care for older patients with depression was greater; they had ever taken care of older patients with depressive symptoms or depression; they had never received in-service training on depression in the past year; and they had ever attended lectures about depression in school. Hospital nurses' knowledge about late-life depression was limited, and they had neutral to slightly favorable attitudes about depression in Taiwan. It is suggested to carefully examine and evaluate in-service training related to depression for nurses in hospitals. In addition, developing appropriate interventions to increase hospital nurses' knowledge level of late-life depression and attitudes toward depression is recommended.